Transborder cooperation of ukrainian and russian: information dimension - Тихомирова, Євгенія Борисівна; Tykhomyrova, E. B. (Центр гуманитарных исследованний «Социум», 2013)
The article is devoted to the information support problems of the Ukrainian-Russian border cooperation and European region information policy tendencies on the level of proper border areas and regions, including information exchange with the help of web-pages and Mass Media publications. The author claims that the traditional and the newest information technologies are actively used. The information is disseminated not only about the general European region characteristics but also about the specific economical, investment and trade proposals, the links on the leading organizations and regional institutions are sited and address distribution of the information material is realized.
Keywords: European regіon; European institutions; information dimension; post-Soviet states; East border; integration processes; the CIS; East Slavic transborder cooperation zone; Russia; Ukraine